1982
DOI: 10.2113/gsecongeo.77.4.764
|View full text |Cite
|
Sign up to set email alerts
|

The f O2 -T and f S2 -T stability relations of hedenbergite and of hedenbergite-johannsenite solid solutions

Abstract: Clinopyroxene in mineralized skarns appears to place local chemical controls on ore mineral precipitation by entering into oxygen-and sulfur-buffering reactions in which garnet is an end product. Prior to investigating these reactions experimentally, the compositions of clinopyroxenes and garnets from ten polymetallic (Zn, Cu-Pb-Zn, Fe-Cu, Zn-Cu, and Fe) skarp. s in the southwestern United States, Japan, and Italy were analyzed with an electron microprobe. The clinopyroxenes are members of the hedenbergite (Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 6 publications
2
29
0
Order By: Relevance
“…This could be explained by the replacement of diopside-hedenbergite by pyrite, pyrrhotite, magnetite, and andradite, which show the change in the system leading to garnet, magnetite and iron sulfides deposition (Fig. 6g, h, and i) according to reactions (1) and (2) (Burton et al, 1982): (2006), the (Fe, Mn)-Mg interdiffusion coefficient is strongly fO 2 sensitive. More oxidizing conditions would favor the formation of andradite and diopsidic clinopyroxene relative to hedenbergite (Gamble, 1982;Gustafson, 1974).…”
Section: Physicochemical Conditions Of Prograde Skarn Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be explained by the replacement of diopside-hedenbergite by pyrite, pyrrhotite, magnetite, and andradite, which show the change in the system leading to garnet, magnetite and iron sulfides deposition (Fig. 6g, h, and i) according to reactions (1) and (2) (Burton et al, 1982): (2006), the (Fe, Mn)-Mg interdiffusion coefficient is strongly fO 2 sensitive. More oxidizing conditions would favor the formation of andradite and diopsidic clinopyroxene relative to hedenbergite (Gamble, 1982;Gustafson, 1974).…”
Section: Physicochemical Conditions Of Prograde Skarn Formationmentioning
confidence: 99%
“…Due to the lack of more complete experimental data on clinopyroxene solid solutions, it is not possible to offer the stability fields of type II (Di 62 Hd 36 Joh 2 ) and type III (Di 24 Hd 54 Joh 22 ) clinopyroxenes. However, as pointed out by Gamble (1982) and Burton (1982), manganese is far more effective than magnesium at expanding the clinopyroxene stability field. Gamble (1982) showed that at 2 kb, Di 75 Hd 25 coexisting with 4 6 2 3 7 3 5 1 Type II II I II II II II II II Note: And-andradite, Gro-grossular, Alm-almandine, Pyr-pyrope, Spe-spessartine.…”
Section: Physicochemical Conditions Of Prograde Skarn Formationmentioning
confidence: 99%
“…Hydrothermal synthesis of hedenbergite was performed by Nolan (1969), Rutstein and Yund (1969), Turnock et al (1973), Gustafson (1974), Kinrade et al (1975), Burton et al (1982), Haselton et al (1987), Moecher and Chou (1990), Raudsepp et al (1990), Perkins and Vielzeuf (1992), Kawasaki and Ito (1994), Zhang et al (1997) and Redhammer et al (2000). The stability of hedenbergite at 0.2 GPa as a function of temperature and oxygen fugacity was determined by Gustafson (1974) and Burton et al (1982). Naturally occurring petedunnite was first described by Essene and Peacor (1987) from Zn skarns in Franklin, New Jersey.…”
Section: Hedenbergitementioning
confidence: 99%
“…Einaudi and Burt, 1982;Einaudi, 1977). Compositional variations within an in dividual grain may even occur, although zona tion patterns within single grains are not always systematic (Burton et al, 1982;Nakano, 1982;Meinert, 1987 Samples analyzed in this study were collected from seven Japanese metalliferous skarn deposits. Most of these were clinopyroxene skarn with small amounts of secondary am phibole replacing clinopyroxene and trace amounts of interstitial calcite and/or quartz.…”
Section: Introductionmentioning
confidence: 99%